An Optical Approach for the Determination of Droplet Volumes in Nanodispensing. (23rd March 2009) - Thurow, Kerstin; Krüger, Thomas; Stoll, Norbert
Abstract : This paper looks at the use of drop-on-demand technology in automated life science laboratories. One significant feature of the droplets generated is the enormously high uniformity under constant conditions. However, there is also a relatively strong dependency on environmental conditions. Many different kinds of liquids are used in laboratory applications, some with unknown properties in advance. In light of this and the special way in which the droplets are created, there is one major question which needs answering in relation to the use of this technology in the area of laboratory automation: What is the volume of the drops generated? This paper will present a solution which can be applied in practice. Besides the technical implementation demonstrated, further alternatives will also be presented. Ultimately, dosing systems with greater autonomy should result from the optimizations demonstrated in this paper.